PARTISIPASI MAHASISWA DALAM EVALUASI PROGRAM PELATIHAN KEPEMIMPINAN MAHASISWA BADAN EKSEKUTIF MAHASISWA FAKULTAS KEGURUAN DAN ILMU KEPENDIDIKAN (BEM FKIP) UNIVERSITAS RIAU - Jefri Novemprasi Sinaga; Daeng Ayub; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this study is How high is student participation in evaluating the leadership training program of BEM FKIP UNRI ?. This research produces data that can determine the level of student participation in evaluating the leadership training program of BEM FKIP UNRI. The benefits of this research include being able to assist and facilitate action taking, especially in improving the evaluation of the BEM FKIP UNRI leadership training program. This research is descriptive with a quantitative approach. Researchers determine the sample using a simple random sampling technique (simple random sampling). Researchers determined a sample of 68 people for research in BEM FKIP UNRI students. This sample was taken according to Sugiyono's table with an error rate of 10% and 20 people for the trial. Retrieval of data in research using a questionnaire. The results of the data analysis showed that the participation of students in evaluating the leadership training program of BEM FKIP UNRI was relatively high. Based on the mean value for the student participation variable in evaluating the leadership training program of BEM FKIP UNRI, it is classified as high with Mean 3.97 and SD 0.8. The interpretation obtained for each indicator of student participation in evaluating the leadership training program of BEM FKIP UNRI is relatively high. So, the most dominant of these 5 indicators is support with a mean number of 4.06 with SD 0.79. So it can be interpreted as a member of BEM FKIP UNRI students who are in a position that is suitable with their abilities when training, although it is not yet optimal. Key Words: Participation, Student Leadership Training